COPS STRATEGY: A STRATEGY TO TEACH WRITING SKILL - Fitri Novia (Universitas Ahmad Dahlan)
The purpose of this study was to find out whether or not there was a significant difference in writing achievement between students who were taught through COPS strategy and that of those who were not. The sample of the study was 71 students of SMP N 1 Sungai Pinang Ogan Ilir. Purposive sampling technique was used to select the sample. Written test was used to collect the data which consisted of five topics. T-test was used to analyze the data. Based on the result, it was found that the t-obtained (6.450) was higher than t-table (1.950) and the àvalue (0.000) was lower than Pvalue (0.05), the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It meant that there was a significant difference in writing achievement between students who were taught by through COPS Strategy and that of those were not. Thus, COPS strategy can be used to teach writing skill.